Implications of community forest management for the conservation of the genetic diversity of big-leaf mahogany (Swietenia macrophylla King, Meliaceae) in the Maya Biosphere Reserve, Petén, Guatemala - Alarcón-Méndez, M.; Maselli, S.; Zonneveld, Maarten van; Loo, J.; Snook, L.; Oliva, A.; Franco, A.; Duminil, J. (Elsevier, 2023)
Community Forest Management in the Maya Biosphere Reserve (MBR; Petén, Guatemala) has been recognized internationally for yielding forest conservation and socioeconomic benefits. However, the effect of current timber harvesting practices on the genetic diversity of timber species populations has not previously been documented. This study assessed the effects of timber harvesting on the genetic diversity and viability of regeneration of the most commercially important timber species in the MBR: big-leaf mahogany (Swietenia macrophylla King). Trees and seeds were sampled for two consecutive years in two Forest Management Units of the Multiple Use Zone (MUZ) of the MBR: Cruce a la Colorada and Carmelita. We correlated genetic diversity parameters (as measured using nuclear microsatellites) with seed germination percentages and compared genetic diversity of adults and seeds in stands that had been affected by timber harvesting and those that had not. We found a significant correlation between seed germination percentages (81–83%) and observed heterozygosity (rho=0.27), confirming that genetic diversity is important to regeneration success. No significant differences were found in allelic richness (AR), expected and observed heterozygosity (HE and HO), or inbreeding (FIS), between adults and seeds in harvested vs. undisturbed stands; or before and after timber harvesting. We found low inbreeding levels (FIS=0.040–0.094), low biparental inbreeding (0–0.01), and high outcrossing rates (0.925–0.970) in the populations of S. macrophylla analyzed. Our study therefore provides evidence that genetic diversity in big-leaf mahogany populations was not diminished by one cutting cycle under current practices of community forest management in the MUZ of the MBR.